Sterilization of biotic pests by microwave radiation - Novotný, Miloslav; Škramlik, Jan; Šuhajda, Karel; Tichomirov, Vladimír (Elsevier, 2013)
Some of the issues connected to timber structures are caused by wood-destroying insects. The sterilization of timber elements affected by wood-destroying insects with the help of microwaves removes the deficiencies of other available methodologies. Hence the given paper deals with the experimental sterilization of wood-destroying insect by the application of microwave radiation. It explains the principles behind heating with microwaves and also describes the biological effects of microwave radiation in a simplified manner. The following chapter introduces the equipment required for microwave sterilization to take place and the actual experimental sterilization process. In the final part of the paper are the results of the experimental activity. Throughout the experiments it was found out that microwave radiation seems to be an effective methodology to sterilize wood-destroying beetles. Within the conclusion the intensity of microwave radiation needed for a successful and effective sterilization process is recommended together with the time along which the timber element must have a constant temperature achieved by heating in the primary phase.

Some of the issues connected to timber structures are caused by wood-destroying insects. The sterilization of timber elements affected by wood-destroying insects with the help of microwaves removes the deficiencies of other available methodologies. Hence the given paper deals with the experimental sterilization of wood-destroying insect by the application of microwave radiation. It explains the principles behind heating with microwaves and also describes the biological effects of microwave radiation in a simplified manner. The following chapter introduces the equipment required for microwave sterilization to take place and the actual experimental sterilization process. In the final part of the paper are the results of the experimental activity. Throughout the experiments it was found out that microwave radiation seems to be an effective methodology to sterilize wood-destroying beetles. Within the conclusion the intensity of microwave radiation needed for a successful and effective sterilization process is recommended together with the time along which the timber element must have a constant temperature achieved by heating in the primary phase.
Sterilization of biotic pests by microwave radiation
Keywords: Sterilization; microwave radiation; wood (timber); biotic pests; wood-destroying beetle (insect).; Sterilization; microwave radiation; wood (timber); biotic pests; wood-destroying beetle (insect).